A manual for blood conservation - Thomas, Dafydd; Thompson, John; Ridler, Biddy (Tfm Pub., 2005)
Blood conservation has moved up the political and medical agenda. What was once a backwater of research is now a high priority area for doctors, patients and even governments as evidenced by national directives issued over recent years. Good quality research has shown the value of careful blood transfusion policies, which should be part of all clinical governance programmes.